2021
DOI: 10.2147/rmhp.s289782
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Anxiety, Stress, and Coping Styles in Nurses in Emergency Departments and Fever Clinics: A Cross-Sectional Survey

Abstract: Background During the Coronavirus Disease 2019 (COVID-19) pandemic, emergency departments and fever clinics nurses acted as gatekeepers to the health care system. To manage the psychological problems that these nurses experience, we should develop appropriate training and intervention programs. Objective To identify the impact of COVID-19 on the psychology of Chinese nurses in emergency departments and fever clinics and to identify associated factors. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
2
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 39 publications
10
119
2
3
Order By: Relevance
“…According to previous studies from SARS and Ebola pandemic, the onset of a sudden /immediately life-threatening illness could lead to extraordinary amount of pressure on healthcare workers ( Liu et al, 2012 ). SAS score which was developed by professor Zung ( Zung, 1971 ) has been extensively used as a simple tool for evaluating level of anxiety in clinics due to its good reliability and validity ( Cheng et al, 2020 , Cui et al, 2021 , Li et al, 2021 , Mo et al, 2021 ). Recently, many studies evaluated the impact of COVID-19 on development of anxiety in the frontline nurses.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies from SARS and Ebola pandemic, the onset of a sudden /immediately life-threatening illness could lead to extraordinary amount of pressure on healthcare workers ( Liu et al, 2012 ). SAS score which was developed by professor Zung ( Zung, 1971 ) has been extensively used as a simple tool for evaluating level of anxiety in clinics due to its good reliability and validity ( Cheng et al, 2020 , Cui et al, 2021 , Li et al, 2021 , Mo et al, 2021 ). Recently, many studies evaluated the impact of COVID-19 on development of anxiety in the frontline nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of infection; especially spreading it to family members, long shifts in sub-optimal condition, lack of training and confidence created a vicious cycle of mistrust and negative professional attitude among physicians and nurses [28]. For example a study from china showed that mental health problems were more likely among nurses who regretted being in the field during the pandemic [29]. Another systematic review and meta-analysis showed high prevalence of anxiety and depression especially among female nurses [25].…”
Section: Stigmatizationmentioning
confidence: 99%
“…Pandemics impose an immense psychological burden on healthcare workers due to a combination of workplace stressors and personal fears [13,14], including lack of personal protective equipment (PPE) and other resources, long working hours, exposure to COVID-19-positive patients, fear of spreading the virus to family and relatives, increased workload, isolation, stigmatisation and the loss of a colleague, among others [15,16]. These factors contribute to increased physical and psychological burden on healthcare professionals [17], which can lead to the development of stress, insomnia, depression and/or anxiety [18].…”
Section: Introductionmentioning
confidence: 99%